Fake News Detection Using Machine Learning Algorithm Logistic Regression - Ramya, K; Yamini, M; Jyothirmai, M (International Journal of Computer Sciences and Engineering, 2023)
Machine learning is field of Artificial Intelligence that focuses on the development of algorithms and statistical methods. Fake news has caused a lot of issues for our society. Many researchers are trying to determine what fake news is. It is challenging to recognize ambiguous fake news, can only be found after determining meaning and recent pertinent facts. For news, everyone uses a variety of online sources. News quickly disseminated among millions of users in a very short period of time to the increase in the use of social media platforms like Facebook, Twitter, etc. We will enable the user to categorize news as either genuine or real. The logistic regression approach will be used to identify false news. Natural Language processing techniques like Term Frequency Inverse Document Frequency (TF-IDF), text processing etc. In our experiment, we`ll demonstrate how our method boosts bogus news` overall performance. We are providing URL search whether the given URL is fake or not.